Remote photobiomodulation ameliorates behavioral and neuropathological outcomes in a rat model of repeated closed head injury - Chongyun Wu; Meng Li; Zhe Chen; Shu Feng; Qianting Deng; Rui Duan; Timon Cheng-Yi Liu; Luodan Yang (Translational Psychiatry)
Abstract Repeated closed-head injuries (rCHI) from activities like contact sports, falls, military combat, and traffic accidents pose a serious risk due to their cumulative impact on the brain. Often, rCHI is not diagnosed until symptoms of irreversible brain damage appear, highlighting the need for preventive measures. This study assessed the prophylactic efficacy of remote photobiomodulation (PBM) targeted at the lungs against rCHI-induced brain injury and associated behavioral deficits. Utilizing the “Marmarou” weight-drop model, rCHI was induced in rats on days 0, 5, and 10. Remote PBM, employing an 808 nm continuous wave laser, was administered daily in 2-min sessions per lung side over 20 days. Behavioral deficits were assessed through three-chamber social interaction, forced swim, grip strength, open field, elevated plus maze, and Barnes maze tests. Immunofluorescence staining and 3D reconstruction evaluated neuronal damage, apoptosis, degeneration, and the morphology of microglia and astrocytes, as well as astrocyte and microglia-mediated excessive synapse elimination. Additionally, 16S rDNA amplicon sequencing analyzed changes in the lung microbiome following remote PBM treatment. Results demonstrated that remote PBM significantly improved depressive-like behaviors, motor dysfunction, and social interaction impairment while enhancing grip strength and reducing neuronal damage, apoptosis, and degeneration induced by rCHI. Analysis of lung microbiome changes revealed an enrichment of lipopolysaccharide (LPS) biosynthesis pathways, suggesting a potential link to neuroprotection. Furthermore, remote PBM mitigated hyperactivation of cortical microglia and astrocytes and significantly reduced excessive synaptic phagocytosis by these cells, highlighting its potential as a preventive strategy for rCHI with neuroprotective effects.